Multidisciplinary management of chronic pain in elderly oncology patients - Pysz-Waberski, Dariusz; Sadurska, Joanna; Kędzierska-Jamróz, Joanna; Pietrzyński, Łukasz; Lorek, Andrzej; Jarosz, Magdalena; Gisterek, Iwona (Contemporary Oncology/Współczesna Onkologia, 2022)
Chronic pain is one of the most common and most bothersome symptoms in cancer patients, which occurs especially often in the elderly population. Although methods of pain treatment are well known, it is not uncommon for individuals with chronic or terminal illnesses to remain underdiagnosed or untreated. Effective pain management has become the measure of success in oncology therapy. For this reason, effective pain management has become an indispensable success factor of multidisciplinary oncological therapy. Along with the growing interest in the holistic approach in medicine, and hence in interdisciplinary treatment, the management of cancer pain in older patients was presented.